The Evaluation of Seismic Fragility Curves for High-rise RC Frames - Kyaw, Cho Wai Phyo; Mon, Khin Aye (The Indonesian Institute of Science and Technology Research, 2025)
In Yangon City's downtown area, Latha Township is a congested area with a high population density. Most of the buildings in the downtown area are RC residential buildings. Yangon is regarded as a medium seismicity region and is about 40 km west of the Sagaing Fault, which is a major active fault in Myanmar. For disaster seismic risk reduction on human lives and infrastructure, this study evaluates the seismic performance of high-rise reinforced concrete buildings under Service Level Earthquake (SLE), Design Basis Earthquake (DBE), and Maximum Considered Earthquake (MCE) hazard levels. The first objective is to evaluate the seismic performance of such buildings with varying length-to-width ratios under possible future earthquakes by using the mean values of maximum %ISDR, following FEMA 356 criteria. The second objective is to develop fragility curves based on results obtained from Incremental Dynamic Analysis (IDA) using SAP 2000. Hypothetical building models represent structures in Latha Township with material properties aligned with current construction practices, as informed by the Yangon City Development Committee (YCDC). Nonlinear Time History Analysis (NTHA) evaluates seismic performance, correlating inter-story drift ratios (%ISDR) with ground motion intensities, specifically peak ground acceleration (PGA). Nonlinear properties are modeled in compliance with ASCE 41-13 guidelines. This analysis aims to provide a risk transfer measure for those vulnerable high-rise structures in order to protect the properties of residents under possible future earthquakes.